New occurrence of a macro B-chromosome in Astyanax scabripinnis paranae (Pisces, Characiformes, Characidae) - Maistro, E. L. [UNESP]; Foresti, F. [UNESP]; Oliveira, C. [UNESP] (My University, 1994)
Cytogenetic studies performed on 17 specimens (11 females and six males) of Astyanax scabripinnis paranae from the Cascatinha stream showed that this population has 2n = 50 chromosomes (8M + 22SM + 10ST + 10A), two chromosome pairs with NORs and conspicuous C-band positive blocks in the terminal position of the long arm of five chromosome pairs. Three females presented 2n = 51 chromosomes and the extra chromosome was a large metacentric similar in size and morphology to the first chromosome pair in the karyotype. This accessory chromosome was entirely heterochromatic in C-banded metaphases, which permitted its classification as a supernumerary chromosome. Some aspects related to the morphology of such macro B-chromosomes are discussed.
Keywords: animal cell; chromosome analysis; female; fish; karyotype; male; nonhuman; supernumerary chromosome